Pengembangan Media Pembelajaran Ular Tangga Untuk Peningkatan Edupreneurship Siswa Pada Materi Aritmatika Sosial - Badriyyah, Lu'luatul; Khofya Haqiqi, Arghob (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2023)
Education has an important role in the world of entrepreneurship and job creation. According to the results of the initial analysis carried out, students' entrepreneurial competence is relatively low, so there is a need for relevant entrepreneurship education in learning media that can increase students' entrepreneurial competence, one of which is the existence of Social Arithmetic Snakes and Ladders media for Increasing Edupreneurship. So this research aims to develop learning media and analyze the validation of design results for developing snakes and ladders learning media to increase student education in social arithmetic material. This research uses Research and Development (R&D) with the Thiagarajan 4D development model consisting of Define, Design, Development and Dissemination. The data collection technique used was validation questionnaires from material experts, media experts, edupreneurship experts, and student response questionnaires. The development results obtained are the Snake and Ladder Media product for increasing student education in social arithmetic material. The results of the research were obtained from the validation results of material experts getting a mean of 4.21, media experts getting a mean of 4.33, edupreneurship experts getting a mean of 4.71 and student responses through limited scale development trials with a mean score of 96%. Based on these data, it can be concluded that the media is declared very suitable for use as a mathematics learning medium to support the mathematics learning process and increase edupreneurship, especially at SMPN 2 Kaliwungu Kudus.